Design of frequency reconfigurable 2 by 8 linear array antenna structure / Rodiah Mahmud - Mahmud, Rodiah (2013)
Reconfigurability in antenna system is a desired characteristic that has been the focus of much in recent year. This paper presents a frequency reconfigurable 2 by 8 linear array antenna structure integrated with radio frequency (RF) switches. The 2 by 8 corporate feed linear array antennas was existing designed at 2.4GHz and simulated by using of Computer Simulation Tool (CST). After fabricated, the prototype antenna was constructing with RF switching circuit. RF switching circuitry involves two RF PIN diodes which located on the left and right side feeding line of the antenna structure in order to activate array of patch. The four of frequency can be simply obtained by configured switching the PIN diodes on and off. The simulation and measurement result of frequency based on the different element array structure are presented.